Partial purification and characterisation of S-adenosylmethionine:protein-histidine N-methyltransferase from rabbit skeletal muscle - Vijayasarathy, C.; Narasinga Rao, B.S. (Biochimica et biophysica acta, 1987)
A new class of protein methylase ( S-adenosylmethionine: protein-histidine N-methyltransferase) which methylates histidine residues of protein substrates using S-adenosylmethionine as the methyl donor has been partially purified from rabbit skeletal muscle, 22-fold with a yield of 56%. The enzyme activity was monitored using denatured myofibrils from young rabbit skeletal muscle as the methyl acceptor protein substrate. The enzyme was localised in the myofibrillar fraction and myofibrils isolated in pure form represented the enzyme-substrate complex. The enzyme was solubilised in 0.275 M KCl. The methylase showed no requirement for any metal ion and has a pH optimum of 8.0. It was shown to require a reducing agent like mercaptoethanol for its activity. It was also shown that cardiac and skeletal muscle forms of actins obtained from different species serve as the efficient methyl acceptor protein substrates. Since the enzyme was found to methylate specifically the histidine residues of actin we propose to designate this new methylase as protein methylase IV, to distinguish it from the already known protein methylases I, II and III.